Customer Loyalty Approach to Product Quality, Price and Promotion - Andriyan; Gemina, Dwi; Pramestidewi, Chandra Ayu; Gemini, Pra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze and identify the influence of product quality, price and promotion, whether they have a direct and positive influence or not on PT customer loyalty. Agronesia Saripetojo. The questionnaire was distributed to 100 respondents who were taken by selecting a sample using purposive sampling technique. The questionnaire was tested with an validity test, an irreliability test, and also a classical assumption test. iThe results of the test are valid, irreliable, and can be used as regression data. The analysis method used in this research is the descriptive method and path analysis with an quantitative approach. iThe results of the research show that 1) product quality, price and promotion have a direct and positive influence on customer loyalty, i2) price and promotion have a direct and positive influence on customer loyalty, 3) product quality has no direct and positive influence on customer loyalty